Capaian Perkembangan Fisik Motorik Dan Stimulasinya Pada Anak Usia 3-4 Tahun - Eka Damayanti; M. Ansar Nasrul (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
This research aims to determine the description of physical motor development in children aged 3 to 4 years based on the child development achievement standard and to formulate an appropriate stimulation. The research was conducted by using a qualitative descriptive approach with two subjects who were 3 to 4 years old. The subjects were selected purposively based on criteria: (1) children aged 3 to 4 years, (2) accessible for the researchers, (3) Willing to be the subject of research. Data were collected by using observation and interview techniques and then analyzed descriptively. The result this study showed that two children have met the achievement of physical motor development. The stimulation that parents have done namely : (1) let the children do something which could help them develop their motor skills; (2) Give a praise-shaped appreciation for their achievement development; (3) supervise the child when conducting activities that may develop their motor skills; (4) help the child in the process of development.